Dietary interventions for fetal growth restriction – therapeutic potential of dietary nitrate supplementation in pregnancy. (27th February 2017) - Cottrell, Elizabeth; Tropea, Teresa; Ormesher, Laura; Greenwood, Susan; Wareing, Mark; Johnstone, Edward; Myers, Jenny; Sibley, Colin
Abstract : Targeting the nitrate–nitrite–NO pathway in pregnancy. Endogenous synthesis of NO involves the oxidation ofl ‐arginine by nitric oxide synthase (NOS) enzymes;l ‐citrulline can be converted tol ‐arginine in vivo, providing an alternative means of stimulating this pathway. In the 'alternative NO pathway', inorganic nitrate (derived either from oxidation of endogenous NO or from dietary sources) is reduced in the body to nitrite via bacterial nitrate reductase (NaR) enzymes. Nitrite can then reduced to NO within the circulation and tissues via a host of nitrite reductase (NiR) enzymes, generating NO. In pregnancy, enhancing NO synthesis by either pathway aims to improve uteroplacental blood flow, and hence fetal growth. Abstract: Fetal growth restriction (FGR) affects around 5% of pregnancies and is associated with significant short‐ and long‐term adverse outcomes. A number of factors can increase the risk of FGR, one of which is poor maternal diet. In terms of pathology, both clinically and in many experimental models of FGR, impaired uteroplacental vascular function is implicated, leading to a reduction in the delivery of oxygen and nutrients to the developing fetus. Whilst mechanisms underpinning impaired uteroplacental vascular function are not fully understood, interventions aimed at enhancing nitric oxide (NO) bioavailability remain a key area of interest in obstetric research. In addition to endogenous NO production from the amino acidl ‐arginine, via nitric oxide synthase (NOS) enzymes, research in recent years has established that significant NO can be derived from dietary nitrate, via the 'alternative NO pathway'. Dietary nitrate, abundant in green leafy vegetables and beetroot, can increase NO bioactivity, conferring beneficial effects on cardiovascular function and blood flow. Given the beneficial effects of dietary nitrate supplementation to date in non‐pregnant humans and animals, current investigations aim to assess the therapeutic potential of this approach in pregnancy to enhance NO bioactivity, improve uteroplacental vascular function and increase fetal growth.